Flora at risk in the plant communities of the Ciénaga de La Palmita, Zulia State, Venezuela - Vera, Antonio (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
An inventory of the endangered flora of the deciduous thorny xerophytic shrublands and mangrove forest was conducted in the Wildlife Fauna Reservoir Ciénaga de La Palmita and Isla de Pájaros, Zulia state, Venezuela. The research was carried out through 10 sampling events, plots of 400 m² and 1000 m², and field explorations (2021-2022). The species were classified according to the Red Book of Venezuelan Flora, identifying 23 species and 16 families, grouped into the following categories: Vulnerable (VU) 4 spp., Near Threatened (NT) 8 spp., Least Concern (LC) 8 spp., and Data Deficient (DD) 3 spp. The Cactaceae family had the highest number of species at risk (3), including Acanthocereus tetragonus, Leuenbergeria guamacho, and Melocactus curvispinus, the latter two being listed as Vulnerable. Only one individual of Pseudalbizzia niopoides var. colombiana (Fabaceae), listed as Vulnerable, was recorded. The mangroves Avicennia germinans and Rhizophora mangle were listed as Near Threatened, and Conocarpus erectus was designated as Least Concern. Additionally, taxa endemic to Venezuela, Bromelia humilis (Bromeliaceae) and Evolvulus villosissimus (Convolvulaceae), were found to be Near Threatened and Data Deficient, respectively, due to fires, harvesting for ornamental purposes, and restricted distribution. The medicinal trees Guaicum officinale and Pterocarpus officinalis were listed as Vulnerable and Least Concern, respectively. The orchid Encyclia cordigera was classified as Near Threatened. It was concluded that the number of at-risk species is increasing in the studied Wildlife Fauna Reservoir (ABRAE) due to anthropogenic disturbances currently threatening its flora.